Ethical, legal and administrative implications of the use of video and audio recording in an emergency department in Ontario, Canada. Issue 1 (28th September 2020) - Douglas, Stuart L; McRae, Andrew; Calder, Lisa; de Wit, Melanie; Sivilotti, Marco L A; Howes, Daniel; Brooks, Steven C; Szulewski, Adam
Abstract : While video and audio recording (VAR) of patients is well described for clinical research, its application to quality improvement in the emergency department has thus far been limited and hindered by potential obstacles. We believe this technology holds promise to incite marked systems improvement but only if deployed in a thoughtful and principled manner. Experts in clinical, regulatory, legal, quality improvement, patient safety and ethical domains collaborated to articulate the salient considerations and challenges to implementation of a VAR programme. We describe this implementation using the lens of legislation and other principles specific to our current context. The landscape of ethical, legal and regulatory barriers and a case example of how a VAR programme has been implemented in an emergency department in Ontario, Canada are outlined. The potential to harness VAR data to drive quality and to improve safety is remarkable. Articulating the most contentious issues and illustrating how they can be addressed may guide others hoping to implement similar VAR programmes.